The assessment of argyrophylic nucleolar organizer regions (AgNORs) in gynecological oncology - Bieńkiewicz, Andrzej; Korczyński, Jerzy; Gottwald, Leszek; Danilewicz, Marian (Menopause Review/Przegląd Menopauzalny, 2005)
In the literature the assessment of proliferative activity of the malignant tumour has been found as the potential independent prognostic factor. The number of nucleolar organizer regions (NORs) per nucleus has been found as a good marker of the proliferative activity of various cancers. In the paper we discussed the usefullnes of the AgNOR method in oncology, especially in gynecological oncology.